Index JCS - JCS Volume 1 (Journal of Consumer Sciences, 2016)
JCS VOL 01 NO 01Access Information 54Bawah Market 4Buying Behavior 7CETSCALE 5Complaint Intention 56Composite reliability 23Counseling teachers 28Culture Values 55Domestic 8Ethnocentrism 6Excitement 44Foreign 8Hedonic buying 38Involvement 65MILOV 40Mixture purchase 8Multinomial logistic 8Objective quality 3Parents’ Involvement 67Parents’ Perception 67Pekanbaru 4PERAKS 18Perceived Quality 7Personality factors 19Reference group instrument 40Reputable college 28SEM 18Smart PLS 21SNI 65Toys Purchase Decision 66Toys Purchasing Decision 68Unsatisfied experience 52Value Loss 55 JCS VOL 01 NO 02Access Information 34Attitude 5Behavioral Control 8Buying Intention 50CFI 63CMIN 63Confirmatory Factor Analysis 65Customer Satisfaction 61day cream 45E-Money 6Family Financial Planning 35Financial issue 15Financial Management 19FMCG 58GNNT 7Marketing practitioners 58Motivation 35Need 36Perceived Value 59Restaurant Atmosphere 60Revisit Intention 64RMSEA 63Saving Behavior 20Seaweed 45service space 60Subjective Norm 7TPB 47Use Intention 9